Advanced agro-engineering technologies for rural business development - Kharchenko, Valeriy, 1938-; Vasant, Pandian (Advances in environmental engineering and green technologies (AEEGT) book series., 2019)
"This book explores a series of technological methods and a number of technical means that ensure the organization of production of various products in the territories newly allocated for economic activity. The specified technologies and technical means are adapted to applications in the production of small scale and the enterprises of small and medium business"--